2023
DOI: 10.3390/nu15061359
|View full text |Cite
|
Sign up to set email alerts
|

Liver Lipidomics Analysis Revealed the Novel Ameliorative Mechanisms of L-Carnitine on High-Fat Diet-Induced NAFLD Mice

Abstract: The beneficial effects of L-carnitine on non-alcoholic fatty liver disease (NAFLD) were revealed in previous reports. However, the underlying mechanisms remain unclear. In this study, we established a high fat diet (HFD)-induced NAFLD mice model and systematically explored the effects and mechanisms of dietary L-carnitine supplementation (0.2% to 4%) on NAFLD. A lipidomics approach was conducted to identify specific lipid species involved in the ameliorative roles of L-carnitine in NAFLD. Compared with a norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
(85 reference statements)
0
0
0
Order By: Relevance
“…Notably, the glycerophospholipid metabolic pathway was most pronounced in BPF-induced lipid metabolism disorders. Sun [30] et al found that L-carnitine significantly improved NAFLD in mice by modulating the glycerophospholipid metabolic pathway. Feng [31] et al showed that phytosterols ameliorated HFD-induced metabolic abnormalities and NAFLD in mice by modulating the glycerophospholipid metabolic pathway.…”
Section: Disscusionmentioning
confidence: 99%
“…Notably, the glycerophospholipid metabolic pathway was most pronounced in BPF-induced lipid metabolism disorders. Sun [30] et al found that L-carnitine significantly improved NAFLD in mice by modulating the glycerophospholipid metabolic pathway. Feng [31] et al showed that phytosterols ameliorated HFD-induced metabolic abnormalities and NAFLD in mice by modulating the glycerophospholipid metabolic pathway.…”
Section: Disscusionmentioning
confidence: 99%